Aurignacian industry types and their «fossiles directeurs» in the Carpathian Basin and East Bohemian Massif: a new study attempt - Yuri E. Demidenko; Демиденко Юрій; Demidenko Jurij; Škrdla Petr; Béres Sándor; Rats Adalbert; Рац Адальберт; Rácz Béla (Institute of Archaeology-Slovak Academy of Sciences, 2019)
Abstract. In spite of more than a century long Aurignacian studies in the Carpathian Basin and East Bohemian Massif of the Middle Danube region (since the discovery of Krems-Hundssteig site – Strobl & Obermaier 1909) and even some synthesis works done during last 10 years (e.g. Nigst 2012; Demidenko, Škrdla, Nejman 2017; Chu 2018), understanding of various Aurignacian industries and their specific artifacts (“fossils directeurs / fossil types”) is still far from clear. The present study attempts to summarize some data from the most understandable so far for us sites and their materials on the subject using an Aurignacian sensu stricto chronological-industrial type sequence. Proto-Aurignacian / Aurignacian 0 is the only now Aurignacian industry type that can be placed into the time period preceding Heinrich Event 4 (HE-4) and Campanian Ignimbrite (CI) eruption, ca. 46 000 – 40 000 cal BP, GI-12 – GI-9. Proto-Aurignacian “fossil types” can be seen through the presence of serial bladelet “carinated” cores, lamelles Dufour of Dufour subtype and Krems points. Proto-Aurignacian sites are known in Lower Austria (KremsHundssteig), Romanian Banat (Coşava, Romaneşti-Dumbrăviţa, Tincova), Ukrainian Transcarpathia (Beregovo I), possibly some materials in Vojvodina’s Banat (Crvenka-At) and maybe in Eastern Resava (Orlovača cave, levels 4-3c) in Serbia, as well as in Eastern Slovakia (e.g. Tibava).
Keywords: Carpathian Basin; East Bohemian Massif; «fossiles directeurs»